National Language under VUCA and-BANI World: The Predicament of Teaching Thai Language and Perspectives from Southern Thailand Educational Institutions - Tantasit, Radchadaporn (Journal of Education Culture and Society, 2025)
Aim. The challenge in Development in the education in Thailand is to enhance the efficacy of Thai language acquisition among students while simultaneously transforming the overall Thai language instructional system. this research has two research objectives which have been established. The primary goal is to investigate the viewpoints on Thai language instruction in the modern world. The second objective is to investigate whether teachers of varying ages hold similar or divergent viewpoints on different facets of Thai language instruction. These objectives are intended to provide information for policy proposals concerning Thai language education.Methods. The research utilises a mixed-methods methodology, which involves the integration of quantitative surveys with school administrators (N = 80), teachers (N = 175), and students (N = 170). In addition, qualitative interviews (N = 15) were administered. All participants are situated in in Southern Thailand Educational Institutions. Results. The research found unanimous agreement among the sample group. mostly falling under “strongly agree.” All groups prioritise essential employment skills, intercultural communication, and interdisciplinary integration. Technology integration is crucial, yet viewpoints vary, especially among different age groups of teachers. Younger educators prioritise global communication and language evolution, while older educators prioritise technology adoption. Conclusion. The research findings highlight the urgency of promoting Thai language skills in alignment with the evolving VUCA and BANI world. It suggests revising the education system to equally support Thai language development alongside STEM subjects.